2007
DOI: 10.1016/j.jmatprotec.2006.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of mechanical properties of polyamide components on build parameters in the SLS process

Abstract: Customised properties of parts manufactured using the selective laser sintering process are achievable by variation of build parameters. The energy density, controlled by laser power, distance between scan lines and speed of the laser beam across the powder bed, all have a very strong influence on the density and the mechanical behaviour of the parts. The present paper investigates the influence of the energy density on physical and mechanical properties of parts produced using polyamide. Additionally, the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
351
2
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 514 publications
(391 citation statements)
references
References 10 publications
31
351
2
7
Order By: Relevance
“…Various studies 10,12 have shown that increasing the laser power leads to an increase in mechanical properties (e.g.…”
Section: Infra-red Lamp Powermentioning
confidence: 99%
“…Various studies 10,12 have shown that increasing the laser power leads to an increase in mechanical properties (e.g.…”
Section: Infra-red Lamp Powermentioning
confidence: 99%
“…Ho et al [3] evaluated the effect of the Energy Density (ED) parameter on polycarbonate structures, while a similar approach was adopted by Drummer et al [4,5] and Caulfield et al [6] for the analysis of PA structures. Most of them focussed on the influence of ED on the mechanical performance of laser sintered parts and the main outcome from these studies was that an increase of the ED caused the mechanical properties, especially tensile strength, to improve up to a value where they stabilise or slightly decrease.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the density, and the mechanical properties, of laser sintered nylon-12 parts increase with laser power [10,11]. As laser power increases, melt temperature is raised, viscosity would be expected to reduce, and improved melt flow leads to more effective sintering and higher densification.…”
Section: Density and Porositymentioning
confidence: 99%